2021
DOI: 10.3389/fpsyg.2021.630798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-Compassion Training on Work-Related Well-Being: A Systematic Review

Abstract: Self-compassion, sharing some commonalities with positive psychology 2.0 approaches, is associated with better mental health outcomes in diverse populations, including workers. Due to the COVID-19 pandemic, there is heightened awareness of the importance of self-care for fostering mental health at work. However, evidence regarding the applications of self-compassion interventions in work-related contexts has not been systematically reviewed to date. Therefore, this systematic review aimed to synthesize and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 72 publications
3
46
0
1
Order By: Relevance
“…Importantly, the results showed that only the compassion intervention group demonstrated a significant and moderate increase in self-compassion. These results align with previous studies implying selfcompassion is a coping strategy that can be developed through training (Neff and Germer, 2013;Kirby et al, 2017;Ferrari et al, 2019;Craig et al, 2020;Kotera and Van Gordon, 2021). Thus, when an individual possesses the knowledge and training regarding how to quickly reduce a physiologically stressful response to an emotionally challenging experience, through establishing compassion and confidence within themselves, acting on that knowledge builds resilience to the condition called "empathy distress, " which has been shown to lead to reduced motivation and engagement as well as increased sickleave (Figley, 1995).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, the results showed that only the compassion intervention group demonstrated a significant and moderate increase in self-compassion. These results align with previous studies implying selfcompassion is a coping strategy that can be developed through training (Neff and Germer, 2013;Kirby et al, 2017;Ferrari et al, 2019;Craig et al, 2020;Kotera and Van Gordon, 2021). Thus, when an individual possesses the knowledge and training regarding how to quickly reduce a physiologically stressful response to an emotionally challenging experience, through establishing compassion and confidence within themselves, acting on that knowledge builds resilience to the condition called "empathy distress, " which has been shown to lead to reduced motivation and engagement as well as increased sickleave (Figley, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…Considering the negative effects of mental health problems in the workplace, both regarding individual suffering and organizational costs, effective interventions are indeed needed. Because previous studies on compassion interventions have mainly involved healthcare professionals or employees working in caring-focused environments, evaluating the impacts of compassion training in other work contexts is important (Kotera and Van Gordon, 2021). The findings of the present intervention study contribute to existing knowledge by focusing on professionals in both a public service agency and a private company in the financial sector.…”
Section: Discussionmentioning
confidence: 84%
“…Understanding the relationship between self-compassion and other constructs is important in developing varied approaches for cultivating self-compassion, as self-compassion interventions remain to be further developed [13]. Existing interventions aimed at increasing levels of self-compassion, for example, the Mindfulness Self-Compassion programme [5], rely heavily on meditative techniques.…”
Section: Improving Self-compassion: Interventions and Their Limitationsmentioning
confidence: 99%
“…In general, literature has shown that self-compassion is positively associated with emotional well-being ( Neff et al, 2007 ; Zessin et al, 2015 ), while negatively associated with the experience of life stress and negative affect ( Ying and Han, 2009 ; Diedrich et al, 2014 ; Zhang et al, 2016 ). A systematic review shows that self-compassion training has a positive effect on work-related well-being ( Kotera and Van Gordon, 2021 ). Moreover self-compassion has been shown to have a positive relation with basic needs satisfaction ( Ghorbani et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%